Sociology : a global introduction - Macionis, John J.; Plummer, Kenneth (New York ; London : Prentice Hall Europe, 1998)
This text is a broad introduction to sociology and the practical aspects of sociological investigation.
Previous ed.: i.e. 6th ed. 1997.
Bibliography: p696-721. _ Includes index.
Keywords: Sociology